Transcriptomic Analysis Reveals the Regulation Mechanism of Sporogenesis in Ulva prolifera - Jiang, Jianan; Li, Yahe; Hu, Chaoyang; Zhu, Wenrong; Xu, Nianjun (Frontiers in Marine Science, 2022)
Ulva prolifera, the main causative species of green tide, has drawn much attention. Spore reproduction was one of the main reproduction strategies which could be induced by changing environment factors, but the mechanism of spore formation remain obscure. Here, we cultured U. prolifera (segments) under the optimal sporulation condition, and 4 states in total from vegetative to reproductive were defined. Additionally, the chlorophyll fluorescence and transcriptome analysis were determined at these 4 states. The results showed that: (1) Compared with state I, the photosynthetic capacity (Fv/Fm, Fv'/Fm', rETRmax) and pigment content (Chl a, Chl b, carotenoids) were enhanced in the state II while decreased in state III and IV (the spore formation period); (2) A total of 41058 unigenes were expressed during the spore formation process; (3) Compared with state I, the genes related with photosynthesis, terpenoid backbone biosynthesis and carotenoid biosynthesis were significantly up-regulated in the state II, III and IV while glycolysis was down-regulated in the state I; (4) Some genes of TFs families such as C3H family may be one of the keys regulate genes in the spore formation; (5) 574 of the difference expression genes (DEGs) associated with flagella biosynthesis were annotated according to GO and KEGG Orthology, including 20 unigenes encoding intraflagellar transport proteins (IFTs) which had not been reported in previous transcriptome analysis in U. prolifera. This study provides a new perspective of spore formation at the gene transcriptional level although the detailed transcription regulatory spore formation network remains to be unveiled.